Pengaruh Kualitas Laporan Keuangan Dalam Hubungannya Dengan Pengukuran Kinerja (Studi Kasus pada Pemda Kota Bandar Lampung) - Goenawan GOENAWAN; Bhakti S. Sastranegara; Syamsu Rizal (Universitas Bandar Lampung (UBL), 2012)
The purpose of the writing of this thesis is to determine whether there is influence of the quality of the financial report on local government performance measurement against the city of Bandar Lampung. The Data used in this research is the primary data, i.e. data obtained directly in the form of data documentation, that require further processing and developed with its own understanding by the authors based on existing theories. The results of this study found that the audit results of the CPC Government financial statements Of Bandar Lampung in 2009 stating an opinion with the exception of% u201Cwajar% u201D. Although the audit said was enough, but it is far from achieving the maximum results, because it is still in the reasonable with the exception. Although its financial performance to get the criteria enough, but the quality of its financial reporting has not been fullest. As for measuring the financial performance of local governments, its financial Reports shall be considered qualified in advance so that it can be maximal To analyze financial performance.